The Effectiveness of Education Using Audiovisual Media on the Prevention of Anemia Among Adolescent Girls: A Literature Review - Mardhatillah Marzuki; Frima Elda; Denas Symond (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anemia remains one of the major nutritional problems commonly affecting adolescent girls, with a relatively high prevalence in many countries, including Indonesia. This condition is primarily caused by inadequate iron intake and low adherence to Iron-Folic Acid (IFA) or iron tablet supplementation programs. Limited knowledge and low interest among adolescents in nutrition-related information contribute to poor preventive behaviors. Traditional educational methods, such as lectures, tend to be one-way and less engaging for this age group. In contrast, audiovisual media are considered more effective because they combine visual and auditory elements that make health messages easier to understand and remember. This study aims to review the effectiveness of audiovisual media in preventing anemia among adolescent girls based on recent research findings. This study employed a literature review method by searching articles from Google Scholar, ScienceDirect, and PubMed databases using the keywords “audiovisual education,” “anemia prevention,” and “adolescent girls.” The review process was conducted systematically through four main stages: organization, synthesis, identification, and advanced analysis. Articles were selected based on predefined inclusion and exclusion criteria, including publication year (2020–2025), participants aged 13–19 years, and a focus on the effectiveness of audiovisual media in anemia prevention. Five eligible articles were thematically analyzed to draw conclusions regarding the impact of audiovisual media on adolescents’ knowledge, attitudes, and preventive behaviors toward anemia. The review findings indicated that the use of audiovisual media consistently improved adolescents’ knowledge, attitudes, and motivation in anemia prevention. Several studies reported an increased in adherence to iron supplementation following audiovisual-based educational interventions. This medium was also perceived as more engaging and easier to comprehend compared to conventional approaches. Audiovisual media serve as an effective, engaging, and interactive educational tool to enhance knowledge and promote preventive behaviors against anemia among adolescent girls.